nBioChip, a Lab-on-a-Chip Platform of Mono- and Polymicrobial Biofilms for High-Throughput Downstream Applications - Anand Srinivasan (American Society for Microbiology, 2017)
ABSTRACT Current in vitro techniques for the culture of microorganisms, and particularly of delicate microbial biofilms, are still mostly limited to low-density plates and manual labor and are not amenable to automation and true high-throughput (HT) applications. We have developed a novel fully automated platform for the formation of mono- and polymicrobial biofilms of Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans at the nanoscale level. The nBioChip is robotically printed, robustly handled, and scanned using a standard microarray reader. Using this technique, hundreds to thousands of identical nanobiofilms encapsulated in hydrogel spots were cultured on microscope slides. The spots can withstand the washing steps involved in screening assays. The miniaturized biofilms demonstrated characteristics similar to those displayed by conventionally formed macroscopic biofilms, including (i) three-dimensional architectural features, (ii) synthesis of exopolymeric matrix material, and (iii) elevated resistance to antibiotic treatment. On the basis of our results, the nBioChip can generate reliable high-throughput antimicrobial susceptibility testing (HT-AST) in 12 to 18 h. The chip serves as a proof-of-concept universal platform for high-throughput drug screening and other downstream applications and furthers understanding of microbial interactions in mixed-species communities at the nanoscale level. IMPORTANCE With an estimated 80% of infections being associated with a biofilm mode of growth and the ensuing recalcitrance of these biofilms with respect to conventional antibiotic treatment leading to high mortality rates, there is a dire and unmet need for the development of novel approaches to prevent, treat, and control these infections. Both bacteria and fungi are capable of forming biofilms that are inherently fragile and often polymicrobial in nature, which further complicates treatment. In this work, we showcase a nanobiofilm chip as a convenient platform for culturing several hundreds of mono- or polymicrobial biofilms and for susceptibility testing. This platform enables true ultra-high-throughput screening for antimicrobial drug discovery or diagnostics or for addressing fundamental issues in microbiology.